FORENSIC MEDICAL EVALUATION OF INJURIES RESULTING FROM ROAD TRAFFIC ACCIDENTS INVOLVING MODERN VEHICLES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Road traffic accidents (RTAs) represent one of the most significant medico-legal and public health problems worldwide. According to the World Health Organization, RTAs cause over 1.3 million deaths annually and millions of non-fatal injuries. In recent years, the structure of road trauma has changed due to the implementation of advanced automotive technologies, such as passive and active safety systems, energy-absorbing body materials, and improved vehicle ergonomics. These innovations have altered not only the frequency but also the morphology and mechanisms of injuries. Consequently, the forensic medical evaluation of trauma resulting from modern vehicle accidents requires new diagnostic criteria and interpretive approaches that integrate clinical, biomechanical, and morphological perspectives.